A novel link scheduler for multi Tx/Rx Wireless Mesh Networks - Effendy, J.; Soh, Sie Teng; Chin, K.; Wang, H.; Wang, L. (2016)
This paper considers the problem of deriving a Time Division Multiple Access (TDMA) link schedule for a single-channel, Multi-Transmit or Receive (MTR) Wireless Mesh Network (WMN). This problem is significant because a short schedule means the WMN has a higher network capacity. We first show that an existing solution, called Directed Edge Coloring (DEC), to channel assignment developed for WMNs with multiple transmit and receive capability is isomorphic to a TDMA schedule. This allows us to develop an efficient algorithm called DEC-MTR that derives a TDMA schedule or superframe for use in single-channel MTR WMNs. In addition, we propose a method to increase the number of links activated in each slot. We compare DEC-MTR against four state-of-the-art schedulers: DEC, Algo-1, HWF and MDF. Experiment results show that DEC-MTR produces equal superframe lengths with up to 23% higher capacity as compared to DEC, and up to 50% shorter superframe lengths as compared to Algo-1, HWF, and MDF with up to 58% higher capacity.